Exploitation of gene(s) involved in 2,4-diacetylphloroglucinol biosynthesis to confer a new biocontrol capability to a Pseudomonas strain - Fenton, A.M. (University College, Cork, Ireland); Stephens, P.M; Crowley, J; O'Callaghan, M; O'Gara, F (Applied and Environmental Microbiology, 1992)
Tn5 mutagenesis and complementation analysis were used to clone a 6-kb genomic fragment required for biosynthesis of 2,4-diacetylphloroglucinol (Phl) from fluorescent Pseudomonas sp. strain F113. A recombinant plasmid, pCU203, containing this region partially complemented a Phl production-negative mutant (F113G22) derived from strain F113. When sugar beet seeds were sown into an unsterilized soil, in which sugar beet was subject to damping-off by Pythium ultimum, the emergence of sugar beet seeds inoculated with strain F113 was significantly greater than that of seeds inoculated with F113G22. Transfer of pCU203 into eight other Pseudomonas strains conferred the ability to synthesize Phi in only one of these strains, Pseudomonas sp. strain M114. Strain M114(pCU203) showed enhanced antagonism towards P. ultimum in vitro and significantly increased the emergence of sugar beet seeds in the same soil compared with emergence induced by the parent strain M114